Prophetic halal food dietary model among International Islamic University Malaysia (IIUM) students - Che Adnan, N. N.; Jamaludin, Mohammad Aizat; Hashim, Yumi Zuhanis Has-Yun (HH Publisher, 2025)
Modern lifestyles, particularly among students, have led to a variety of health issues due to poor nutrition and inappropriate eating habits. This article highlights the importance of dietary practices rooted in the teachings of the Prophet Muhammad (PBUH), which advocate for the consumption of Sunnah-based products to be incorporated in halal food dietary practices among International Islamic University Malaysia (IIUM) students, specifically among Kulliyyah of Engineering students at Gombak, Kulliyyah of Dentistry, Kulliyyah of Nursing and Kulliyyah of Medicine students at Kuantan. This article utilizes a library-based approach. This methodology explores an extensive review of relevant literature and existing research on prophetic dietary practices, nutritional science, and health outcomes associated with different dietary patterns. By analysing scholarly articles, religious texts, and previous studies, this article builds a strong foundation for the proposed prophetic halal dietary model to these selected groups of students. The study also aims to highlight the critical need for students in implementing a dietary framework that aligns with both Islamic teaching and evidence-based modern science. IIUM is an established university that upholds the Sejahtera Academic Framework (SAF) that integrates the spiritual and ethical values into all aspects of student’s life. It is recommended that the university authority implement the prophetic halal food dietary model, as it may help IIUM students adopt effective attitudes and behaviors in their learning process, foster a healthier lifestyle, and maintain holistic well-being.